2023
DOI: 10.3390/agronomy13061522
|View full text |Cite
|
Sign up to set email alerts
|

Water Management for Sustainable Irrigation in Rice (Oryza sativa L.) Production: A Review

Abstract: In the face of the negative impacts of climate change and the accelerated growth of the global population, precision irrigation is important to conserve water resources, improve rice productivity and promote overall efficient rice cultivation, as rice is a rather water-intensive crop than other crops. For several decades, various water conserving technologies have been studied in order to significantly increase water use efficiency (WUE). The objective of this paper is to review the main technologies and appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 123 publications
0
3
0
Order By: Relevance
“…Under AWD conditions, rice fields are drained for a certain period in which the field obtains a certain level of moisture and are then re-flooded. It has been reported that using AWD water technology saves about 23% of the water used for rice irrigation when compared to CF practices [ 8 , 40 ]. AWD technology has the potential to reduce greenhouse gas (GHG) emissions, particularly methane (CH 4 ) gas [ 38 , 44 ].…”
Section: Different Water Management Practices For Rice Cultivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Under AWD conditions, rice fields are drained for a certain period in which the field obtains a certain level of moisture and are then re-flooded. It has been reported that using AWD water technology saves about 23% of the water used for rice irrigation when compared to CF practices [ 8 , 40 ]. AWD technology has the potential to reduce greenhouse gas (GHG) emissions, particularly methane (CH 4 ) gas [ 38 , 44 ].…”
Section: Different Water Management Practices For Rice Cultivationmentioning
confidence: 99%
“…One widely used rice irrigation method around the globe is continuous flooding (CF). However, CF results in unproductive water loss such as seepage, evaporation, and percolation [ 7 , 8 , 9 ]. To overcome unproductive water loss and maintain a high rice yield, water-saving irrigation methods have recently been introduced.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of AWD stands out due to its intermittent and controlled application of floods throughout the rice growing cycle. This approach allows for a reduction in overall water usage while ensuring that the rice crop receives an appropriate amount of water during critical stages of production to prevent negative impacts on yield and grain quality [6,7].…”
Section: Introductionmentioning
confidence: 99%